Fish species, relative abundances and environmental associations in small rivers of the Mae Klong River basin in Thailand - Tongnunui, Sampan; Beamish, Frederick W.H.; Kongchaiya, Chunte (Agriculture and Natural Resources, 2016)
Fish species were collected by electrofishing from 96 sites, representing 79 species, in lightly exploited rivers in western Thailand. Significant chemical and physical environmental factors associated with species numbers and total fish abundance were identified using multiple linear regression. Total abundance correlated negatively with water depth and temperature (r = 0.4, p < 0.05), whereas species numbers correlated positively with river discharge and negatively with elevation (r = 0.6, p < 0.05). Chemical and physical factors that significantly influenced species distribution were determined using partial least squares regression analysis, (p < 0.05; axes 1, r = 0.8; axes 2, r = 0.85), and included elevation, river discharge, width and depth as well as ambient oxygen, alkalinity and pH. Fish were placed into four categories according to their habitat occupancy and abundance and termed; uncommon (54 species), common (16 species), even (8 species) and uneven (1 species), respectively.